The meme culture and the new wave of investors: a study on the power of retail investor sentiments in moving markets - Rasheedh, Ahmed Juman (2022)
The year 2021 began with a highly volatile US Market with retail investors making large gains at the expense of large hedge funds and other instructional investors. At the centre of the spectacle was an unorthodox investment forum, WallStreetBets, on one of the most popular social media, Reddit. The paper utilises a dataset of over 9 million message postings on the Reddit forum to analyse the informational content and effect of the sentimentality of the forum on the market movements. The paper contributes to the growing literature in the field of investor sentiment and behavioural finance.